Pengaruh Komposisi Kompon Ban Dengan Batikan Zig - Zag Terhadap Koefisien Grip Ban Pada Lintasan Beton Kondisi Basah Dan Kering - Arvianto, Muhamad Wijang; , Ir. Pramuko Ilmu Purbo Putro, MT; , Wijianto,S.T.,M.Eng.Sc (2015)
this research aims to know the influence of the composition of compound tires with batikan zig zag - against the tire grip coefficient on the trajectory of the concrete conditions of wet and dry. Composition varied in the manufacture of compounds, namely carbon black and sulfur. The process of making compounds beginning with the preparation of materials to be used, is 10 compositions used are: Rubber Smoke Sheet (RSS), Styrene Butadiene Rubber (SBR), Carbon black, Parafinic Oil, Zinc Oxide (Zno), Stearic Acid (SA), Paraffin Wax, Dibenzothiazly disulfide (MBTS), Cumaron Resin, Sulfur. After that mix all the materials have been prepared. Further compounds the already so with temperature and time of vulcanization presses. Specimen testing does is test of hardness and hardness test with standard SNI 07778:2009, test the grip with the standard ASTM D2047-99. From the results of the test showed that the value of the highest violence at the compound 3. The results of the tensile test of thermal compound manufacturer has a value of voltage drop, from artificial compound thermal compound 1 has a voltage drop the most approaching the compound manufacturer. Then from the results of the test compound grip manufacturer that has the most grip coefficient values are high, but the wear and tear is high, while the compound 3 has a grip coefficient values are low, but the value of low wear and tear. Keywords: compounds, carbon black, sulfur